Sub‐Periosteal Peri‐Implant Augmented Layer Technique to Treat Peri‐Implantitis Lesions. Issue 4 (14th June 2020) - Trombelli, Leonardo; Severi, Mattia; Farina, Roberto; Simonelli, Anna
Abstract : Introduction: The efficacy of surgical regenerative procedures to treat peri‐implantitis lesions has been extensively reviewed. Regenerative treatment showed a variable rate of success, in terms of pocket reduction, gain in bone support, and elimination of signs of infection/inflammation. The aim of the present case report is to illustrate the use of the sub‐periosteal peri‐implant augmented layer (SPAL) technique to correct peri‐implantitis defects Case Presentation: Surgical treatment of three class Ib and one class Ic peri‐implantitis lesions in three patients was performed by means of the SPAL technique. A partial‐thickness flap was elevated, leaving the periosteal layer on the buccal cortical bone plate. The periosteal layer was in turn elevated to create a pouch, which was used to stabilize a bovine‐derived xenograft (deproteinized bovine bone mineral) at the peri‐implant buccal bone defect. No barrier membrane was used. In case of insufficient dimensions of peri‐implant mucosa, a connective tissue graft (CTG) was buccally positioned at the most coronal portion of the implant. Treatment resulted in substantial reconstruction of peri‐implant support associated with reduced probing depth and absence of inflammation. Conclusions: SPAL technique with or without additional CTG may be a suitable option to obtain clinical remission of peri‐implantitis defects associated with buccal bone dehiscence.